HUBUNGAN NEGARA-WARGA DAN DEMOKRASI LOKAL: STUDI KONFLIK TAMBANG DI BIMA - Satriani, Septi (Pusat Penelitian Politik, 2015)
This paper examines the state-citizens relation in a democratic context based on Charles Tilly’s approach. Charles Tilly argues that the degree of democratic regime can be seen based on the state’s capacity to accommodate public engagement. Following Charles Tilly’s argument, a democratic regime provides equal political relation. On the contrary, state-citizen relation in an undemocratic regime is unequal. Based on Charles Thilly’s perspective on state-citizen relations, Lambu’s mining conflict, at district of Bima, West Nusa Tenggara Province is in the intersection category between low capacity democracy and low capacity undemocracy. Keywords: State, Citizen, Relation, Local Democracy.